Incidence rate of different forms of idiopathic childhood focal epilepsy - K. Yu. Mukhin; M. B. Mironov; . .; . .; . .; . .; . .; . . (Эпилепсия и пароксизмальные состояния)
The structure of idiopathic focal forms of epilepsy was investigated on 1118 patients with diagnosis of epilepsy, and aged from the first days of life to 18 years. Their age enabled to monitor the debut of seizures. The methods of investigation included clinical examination, video EEG-monitoring, testing by neuropsychologist and, when necessary, neurovisualization. In 189 cases (16.9% of the total number of patients with the debut of seizures before 18) the idiopathic focal epilepsy forms were diagnosed. In 99 cases (8.8% of patients) the diagnosis was Idiopathic focal epilepsy (IFE) with central temporal spikes. The idiopathic occipital lobe epilepsy (IOE) was found in 47 patients (4.2 % of cases). IFE with pseudo-generalized seizures (IFEPGS) was observed in 31 patients (2.8% of cases). The idiopathic focal epilepsy of infancy (IFEI) was seen in 5 cases which equals to 0.5% of the total patient group. The idiopathic focal epilepsy with affective symptoms (IFEAS) was diagnosed in 7 patients (0.6%). Rolandic epilepsy was most frequently found in the IFE group (52.4% of cases). The idiopathic occipital lobe epilepsy was diagnosed in 24.9% of cases. The IFE-PGS was seen in 16.4% of patients, IFEAS - in 3.7% of cases, and IFEI - in 2.6% of cases. By and large, the results are in line with those obtained in the majority of foreign studies on the incidence rate of the idiopathic focal epilepsy forms.